2009
DOI: 10.1371/journal.pone.0005344
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Hubs in Protein Interaction Networks

Abstract: BackgroundIn spite of the scale-free degree distribution that characterizes most protein interaction networks (PINs), it is common to define an ad hoc degree scale that defines “hub” proteins having special topological and functional significance. This raises the concern that some conclusions on the functional significance of proteins based on network properties may not be robust.MethodologyIn this paper we present three objective methods to define hub proteins in PINs: one is a purely topological method and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
129
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(131 citation statements)
references
References 45 publications
2
129
0
Order By: Relevance
“…2,18 Hence, we used this criterion to identify hubs in our dataset. Further, we defined non-hubs as proteins with one interaction and ignored those with two to four interactions to minimize the effect of potential hubs with unknown interactions.…”
Section: Resultsmentioning
confidence: 99%
“…2,18 Hence, we used this criterion to identify hubs in our dataset. Further, we defined non-hubs as proteins with one interaction and ignored those with two to four interactions to minimize the effect of potential hubs with unknown interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Proteins with a large number of interactions (usually called hubs) are likely to be more essential than proteins with a few links (42). However, there are many criteria to specify hub proteins (43). In this study, we defined the top 8 proteins with the highest number of interactions shown in Fig.…”
Section: Construction Of Wssv Proteinmentioning
confidence: 99%
“…As expected, some differences in the transcription profiles between the hPSC-HEP and liver tissue samples were observed. Moreover, hub proteins [proteins with high level of interactivity that usually are essential and play central role in protein interaction networks (53)], which appear to be involved in the different hepatocyte developmental stages, were identified.…”
mentioning
confidence: 99%